Thermotolerance of Histoplasma capsulatum at 40 °C predominates among clinical isolates from different Latin American regions (2020)
ABSTRACT: The yeast phase of 22 Histoplasma capsulatum clinical isolates from Mexico, Argentina, Colombia, and Guatemala and three reference strains, one from Panama and two from the United States of America (USA), were screened for thermosensitivity characteristics using different analyses. Growth curves at 0, 3, 6, 12, 24, and 30h of incubation at 37 and 40 ◦C, the growth inhibition percentage at 40 ◦C, and the doubling time at 37 and 40 ◦C were determined for all yeasts studied. Most of the isolates examined exhibited thermotolerant phenotypes at 40 ◦C, whereas a thermosensitive phenotype at 40 ◦C was only detected in the Downs reference strain from the USA. Growth inhibition values lower than 33.8% supported the predominance of the thermotolerant phenotype at 40 ◦C. The doubling time means found for the different isolates were 5.14h ± 1.47h at 37 ◦C and 5.55h ± 1.87h at 40 ◦C. This is the first report to underscore the predominance of thermotolerant and delayed doubling time phenotypes in H. capsulatum clinical isolates from different regions of Latin America.